Review on utilization of banana fiber in paper making and its mechanical properties / Nur Afiqah Tajul Arip - Tajul Arip, Nur Afiqah (2021)
In this era, the consumption of paper has increased immensely which are broadly used for writing, packaging, printing, pharmaceutical industries and Fast-moving consumer goods (FMCG). Therefore, possible raw materials are explored to replace the conventional raw materials which is banana fibres. In this study, paper made from banana fibres are focused. Banana fibre, which is a good source of cellulose, is one of the materials that has been discovered to be useful. Due to nonindustrial usage, significant amounts of waste biomass are generated after fruit harvest and dumped as waste. Banana fibre is a high-strength natural fibre that can be combined readily with any other cotton or synthetic fibre to create composite materials like paper. Because banana fibre has a low lignin percentage and a long cellulose fibre with a higher strength, it requires less chemical and energy processing. Banana fibre can be used to make Kraft paper with minor chemical and physical modifications, according to studies.